2021
DOI: 10.1186/s41606-021-00058-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and correlates of sleep quality among undergraduate medical students in Ethiopia: cross –sectional study

Abstract: Purpose Poor quality of sleep has a negative effect on academic performance of medical students. Quantity and quality of sleep in addition to average sleep time are strongly linked with students’ learning abilities, poor academic performance and poor interpersonal relationship which predispose them to mental illnesses. This study is aimed to assess magnitude and correlates of sleep quality among medical students in Ethiopia. Method An institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
4
25
0
4
Order By: Relevance
“…The present study demonstrates a significant association between depression and poor sleep quality. Our study finding is compatible with the study conducted among undergraduate students in Nepal [19], Turkey [34], Ethiopia [35], Saudi Arabia [16], and Brazil [36]. A study from Brazil showed that sleep disruption, insomnia, or less than 7 hours of sleep manifests a cumulative risk ratio of 5.5 for minor psychiatric disorders among medical students [20].…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrates a significant association between depression and poor sleep quality. Our study finding is compatible with the study conducted among undergraduate students in Nepal [19], Turkey [34], Ethiopia [35], Saudi Arabia [16], and Brazil [36]. A study from Brazil showed that sleep disruption, insomnia, or less than 7 hours of sleep manifests a cumulative risk ratio of 5.5 for minor psychiatric disorders among medical students [20].…”
Section: Discussionsupporting
confidence: 91%
“…Six hundred six reproductive age group women were enrolled in this study, which makes a 95.6% response rate. The study participants median (IQR) age was 25 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) years and nearly half (45.7%) were in the age group of 24-33 years. Three hundred sixty (59.4%) of the participant were completed secondary or above education and the majority of the participants were located in the monthly income level of ≤1,500 ETB (Table 1).…”
Section: Socio-demographic Characteristics Of the Study Participantsmentioning
confidence: 99%
“…Despite the growing evidences regarding sleep-related problems in a developed country among reproductive-aged women, the pieces of evidence on developing countries including Ethiopia are limited (32). Besides, most of the available evidences are limited to college students, the general population, pregnant and post-partum mothers (32)(33)(34)(35). Furthermore, to the best knowledge of the authors, there is no prior study, which examined the sleep quality of reproductive age group women in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…19 In another study conducted among undergraduate medical students in Ethiopia, the prevalence of poor sleep quality was found to be 62%. 20 Higher proportion (70.4%) of medical students of Abdulaziz University, Saudi Arabia were found to have poor sleep quality. 21 The variation between different studies might be influenced by variability in methodologies, different study locations, different socio-cultural habits, and different academic pressures among different population groups.…”
Section: Discussionmentioning
confidence: 98%